Evaluation of Administrative Leadership in Colleges of Physical Education and Sports Sciences According to the Total Quality Management Perspective - Kadhim, Ethar (Journal of Physical Education, 2025)
Total Quality Management (TQM) is one of the most important modern concepts that has garnered significant attention from administrative leaders, researchers, and academics in higher education as a prevalent approach in the current period. It is a model of new management that enables administrative leaders to keep pace with and adapt to modern changes because it relies on the application of advanced methods and aims for continuous improvement and development.Therefore, interest in TQM has begun in Iraqi colleges of physical education and sports sciences to achieve multiple objectives by providing a range of educational experiences through its theoretical and applied curricula. It seeks to create a continuous balance between the needs of society and the needs of students. However, we find weaknesses in administrative performance, as it is traditional and tied to systems and laws that restrict the movement of administrations instead of moving towards modernity and keeping pace with the requirements of the times.The aim of this research is to highlight the requirements of administrative leaders in colleges of physical education and sports sciences from the perspective of Total Quality Management (TQM), a modern approach that leads to raising the competencies of their staff. This research was conducted from the perspective of a population of 945 faculty members representing 36 public and private colleges in Iraq. Fifteen requirements were identified. After presenting, analyzing, and discussing the results, the following conclusions were reached  1-The success of TQM hinges on the administrative leader's understanding and belief in this new philosophy.  2-The general opinion of faculty members regarding the evaluation of administrative leaders from a TQM perspective is positive.The researcher recommends the following:  1-Encouraging the administrative leaders of colleges of physical education and sports sciences to adopt the philosophy of TQM as an administrative approach to developing the current and future performance of their colleges. 2- Establishing the leadership team (which will lead the change process) which includes representatives from all parties within the college (professors, employees, students) and specialized experts from outside the college